Perceived Organizational Support and Work Spirit as Predictors of Workplace Happiness: The Mediating Role of Employee Engagement Among Public Hospital Nurses - Ira Widya Sari; Dedi Muhammad Siddiq; Catur Setiya Sulistiyana; Nur Haslina Ramli; Nhan Cam Tri (Indonesian Journal Economic Review (IJER), 2026)
This study examines the effect of perceived organizational support and work spirit on workplace happiness, with employee engagement serving as a mediating variable among nurses at a regional public hospital in Cirebon. A quantitative research design was employed, and data were collected from 166 nurses using structured questionnaires. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate both direct and indirect relationships among the variables. The findings indicate that perceived organizational support and work spirit have positive and significant effects on workplace happiness. Furthermore, employee engagement partially mediates these relationships, suggesting that stronger organizational support and higher morale enhance nurses’ engagement, which in turn promotes greater workplace happiness. These results underscore the critical role of supportive organizational practices and morale-enhancing initiatives in fostering engagement and improving nurses’ well-being. This study provides practical implications for hospital management to strengthen perceived organizational support and implement programs that enhance work spirit in order to increase employee engagement and ultimately create a happier and more productive work environment.